2012
DOI: 10.1080/08912963.2011.651468
|View full text |Cite
|
Sign up to set email alerts
|

Lineage ofArxina schwageri(Silvestri, 1928) new genus (Nummulitacea) from Middle Eocene of Egypt and Sultanate of Oman

Abstract: Four species, Arxina parva (Douville, 1930), Arxina cf. schwageri (Silvestri, 1928) A. schwageri (Silvestri, 1928) and Arxina sp. cf. alpina (Douville, 1916) assigned to the newly erected genus Arxina, are recorded from the Middle Eocene of Egypt and Sultanate of Oman. The phylogenetic trend of these species exhibits a progressive increase in the size, a flattening of the test and a general trend of the coalescence of granules which become smaller in size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Based on Nummulites specimens found in the section, Bishay (1966) and Omara et al (1977) assigned the succession at Maghagha to the Late Lutetian and showed that this stage is represented by the Qarara Formation and part of El Fashn Formation. The stratigraphy and geology of the Qarara Formation has been reported in several studies (Boukhary and Abdulla 1985;Moulin, 2011, Lorraine, 2012, Boukhary et al, 2012. Boukhary and Abdulla (1985) that combined paleontological and petrological examination of the Eocene rocks at Maghagha and revealed that the succession belongs to the Nummulites gizehensis gizehensis Zone.…”
Section: Geological Backgroundmentioning
confidence: 81%
“…Based on Nummulites specimens found in the section, Bishay (1966) and Omara et al (1977) assigned the succession at Maghagha to the Late Lutetian and showed that this stage is represented by the Qarara Formation and part of El Fashn Formation. The stratigraphy and geology of the Qarara Formation has been reported in several studies (Boukhary and Abdulla 1985;Moulin, 2011, Lorraine, 2012, Boukhary et al, 2012. Boukhary and Abdulla (1985) that combined paleontological and petrological examination of the Eocene rocks at Maghagha and revealed that the succession belongs to the Nummulites gizehensis gizehensis Zone.…”
Section: Geological Backgroundmentioning
confidence: 81%
“…The limestone is characterized by Thalassinoides horizons and Nummulites gizehensis accumulation. Based on the previous studies, the index planktonic and benthic foraminifera, besides the occurrence of large benthic foraminifera represented by Nummulites gizehensis, assigned this rock unit to upper Lutetian [18,24,41,[50][51][52][53][54][55].…”
Section: Qarara Formationmentioning
confidence: 99%